PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERGAMBAR FLASHCARD PADA MATERI BANGUN DATAR TERHADAP HASIL BELAJAR SISWA KELAS III SDN PELANG LOR 1 KEDUNGGALAR - Annisa Nurul Istiqomah; Nofita Lestariningsih; Aulia Fajar Khasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics learning on plane geometry in elementary schools is often hindered by the abstract nature of the material and limited use of visual media, resulting in suboptimal learning outcomes. This study aims to examine the effect of picture-based flashcard learning media on mathematics learning outcomes regarding plane geometry among third-grade students at SDN Pelang Lor 1 Kedunggalar. A quantitative approach with a quasi-experimental method and Non-Equivalent Control Group Design was employed, involving 30 students in the experimental group and 15 students in the control group determined through total sampling. Data were collected through tests, observation, and documentation using a multiple-choice test instrument that had been tested for validity (30 of 40 items valid), reliability (Cronbach's Alpha = 0.896; high category), difficulty level, and discrimination index. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, paired sample t-test, and independent sample t-test with SPSS 24. Results showed the data were normally distributed and homogeneous (Sig. = 0.125). In the experimental group, the mean learning outcome increased from 65.17 (pretest) to 80.70 (posttest), with a paired sample t-test Sig. (2-tailed) value of 0.000 (< 0.05), while the independent sample t-test on posttest scores between groups showed a Sig. value of 0.000 (< 0.05), so H0 was rejected and Ha accepted. These findings indicate that the use of picture-based flashcard media significantly affects the improvement of mathematics learning outcomes on plane geometry among third-grade students. Flashcard media also proved effective in increasing student engagement, interest, and conceptual understanding through concrete visual presentation.